Power Loss Analysis and a Control Strategy of an Active Cell Balancing System Based on a Bidirectional Flyback Converter - Yu-Lin Lee; Chang-Hua Lin; Shih-Jen Yang (Applied Sciences, 2020)
This research proposes a power loss analysis and a control strategy of an active cell balancing system based on a bidirectional flyback converter. The system aims to achieve an energy storage application with cells connected in 6 series and 1 parrarel (6S1P) design. To reduce the structural complexity, Metal-Oxide-Semiconductor Field Effect Transistor (MOSFET) array commonly used in balancing system is replaced with the photovoltaic Metal-Oxide-Semiconductor (photoMOS) array. Power loss analysis is utilized for the system operating in the proper current to reach higher efficiency. The proposed loss models are divided into conduction loss, switching loss, and copper and core loss of the transformer. Besides, the models are used to estimate the loss of converter operating in different balance conditions to evaluate the system efficiency and verified by the implemented balancing circuit. By way of the loss models, the balancing current can be determined to reach higher efficiency of the proposed system. For further improvement of the balancing process, the system has also applied a control strategy to enhance the balancing performance that reduces 50% maximum voltage difference than traditional cell-to-pack architecture, and 47% balancing duration than traditional pack-to-cell architecture.